2016
DOI: 10.1111/ijd.13344
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of macrophage migration inhibitory factor (MIF) levels in serum and lesional skin of patients with alopecia areata

Abstract: The finding that MIF is increased in serum and lesional skin of AA patients indicates its possible involvement in the pathogenesis of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…MIF was originally identified because of its ability to inhibit the random migration of macrophages in vitro. MIF is expressed in hair follicles, and there is a close association between reduced MIF in hair follicles and the development of alopecia areata, which is an autoimmune disease of the skin [ 59 , 60 ]. Interestingly, treatment with TGF-β1 and LiCl induced the expression of MIF in MSCs, and treatment with MIF induced DPC viability for recruitment of the conduction ability.…”
Section: Discussionmentioning
confidence: 99%
“…MIF was originally identified because of its ability to inhibit the random migration of macrophages in vitro. MIF is expressed in hair follicles, and there is a close association between reduced MIF in hair follicles and the development of alopecia areata, which is an autoimmune disease of the skin [ 59 , 60 ]. Interestingly, treatment with TGF-β1 and LiCl induced the expression of MIF in MSCs, and treatment with MIF induced DPC viability for recruitment of the conduction ability.…”
Section: Discussionmentioning
confidence: 99%
“…There is still controversy over attribution of an anti‐inflammatory role to MIF. Although histological studies have shown significant downregulation of MIF in AA lesions, and several studies from other IP sites also agree on its inhibitory functions, recent findings have implicated a proinflammatory role for MIF …”
Section: How Do Immune Privilege Sites Prevent Natural Killer Cell Acmentioning
confidence: 95%
“…Although histological studies have shown significant downregulation of MIF in AA lesions, and several studies from other IP sites also agree on its inhibitory functions, 50-53 recent findings have implicated a proinflammatory role for MIF. 29,[54][55][56][57][58][59][60][61][62][63] Another less emphasized mechanism for preventing NK cells from attacking the MHC-negative cells is the expression of nonclassical MHC-I proteins such as human leucocyte antigen (HLA)-G and HLA-E. These MHCs play a great role in preserving fetomaternal tolerance and ocular IP, but their contribution to HF privilege remains to be elucidated.…”
Section: How Do Immune Privilege Sites Prevent Natural Killer Cell Acmentioning
confidence: 99%
“…T-cell-mediated immunity, interferons, cytotoxic CD8 T-cells, cytokines, tumor necrosis factor, macrophage migration inhibitory factor, and humoral autoimmune pathology may be important inducers of hair loss in AA. [ 7 8 ] It is known that skin functions are regulated by the immune system. During stress, secreted catecholamines cause skin blood flow reduction and altered immune/inflammatory functions, including lymphocyte circulation, proliferation, and cytokine production.…”
Section: Discussionmentioning
confidence: 99%